1998
DOI: 10.1007/s002210050376
|View full text |Cite
|
Sign up to set email alerts
|

Corrective loops involved in fast aiming movements: effect of task and environment

Abstract: In daily living, we continuously interact with our environment. This environment is rarely stable and living beings show remarkable adaptive capacities. When we reach for an object, it is necessary to localize the position of this object with respect to our own body before programming an adequate arm movement. If the target remains stable, the programmed movement brings the hand near the target. However, what happens when the target suddenly jumps to another position in space? The aim of this work was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
2
6
1
Order By: Relevance
“…While movements were not particularly rapid in Liu and Todorov (600 to 900 ms), their findings are remarkably consistent with previous studies on fast arm movements (Blouin et al, 1995a(Blouin et al, , 1995bTurrell et al, 1998). Indeed, Blouin et al (1995a) observed large directional adjustments toward the displaced target when participants only had to control the direction of shooting, rapid movements (duration of È200 ms).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While movements were not particularly rapid in Liu and Todorov (600 to 900 ms), their findings are remarkably consistent with previous studies on fast arm movements (Blouin et al, 1995a(Blouin et al, , 1995bTurrell et al, 1998). Indeed, Blouin et al (1995a) observed large directional adjustments toward the displaced target when participants only had to control the direction of shooting, rapid movements (duration of È200 ms).…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that while movement duration and mean velocity matched those of Experiment 1, peak velocity was higher in Experiment 1 than in Experiment 2 because of different task constraints (respectively 2.8 m/s and 1.6 m/s as shown by off-line analyses). However, several studies have shown that online adjustments of movement trajectory can be made for movements whose peak velocity exceeds 2 m/s (e.g., Boulinguez & Nougier, 1999;Flanagan, Ostry, & Feldman, 1993;Turrell, Bard, Fleury, Teasdale, & Martin, 1998). Thus, we preferred similar movement durations (È350 ms) in both experiments rather than similar peak velocities, as the latter option would have yielded large differences in movement durations.…”
Section: Experiments 2-shooting Movements (No Stopping On Target)mentioning
confidence: 95%
“…Our finding that the latency of the response is constant also implies that movements are not controlled by strategy 2, according to which adjustments are postponed to a late stage of the movement, as suggested by many who assume that the initial part of the movement is under open-loop control, with online control emerging during the deceleration phase (Elliott et al 2001; Komilis et al 1993; Turrell et al 1998; van der Meulen et al 1990; Woodworth 1899). We found movement corrections near movement initiation.…”
Section: Discussionsupporting
confidence: 53%
“…3): the latency differences in the three subjects were 1, Ϫ1, Ϫ4 ms, respectively. These latency differences are, however, much shorter than the time differences between the ocular movement and hand movement reported in previous studies (Turrell et al, 1998;Engel et al, 2000;Soechting et al, 2001), in which efference copy of the ocular motor command is deemed to be used as an arm motor command. Moreover, considering the transmission time from the motor cortex to the arm muscles [11-12 ms for biceps brachii, 14 -15 ms for the brachioradialis, observed by transcranial magnetic stimulation (Abbruzzese et al, 1994)] and the delay from the oculomotor neuron activity to the eye movement [6 -7 ms, which is estimated from and Gomi et al (1998)], the motor command for the MFR would be generated simultaneously with that for the OFR or even earlier.…”
Section: Mfr Initiation Mechanismcontrasting
confidence: 53%
“…Recent eye-hand coordination studies (Prablanc et al, 1979;Herman and Maulucci, 1981;Biguer et al, 1982;Fischer and Rogal, 1986;Henriques et al, 1998Henriques et al, , 2003Turrell et al, 1998;Engel et al, 2000;Soechting et al, 2001;Ariff et al, 2002) suggest a couple of possibilities that the MFR could be affected by the OFR, both of which were indeed elicited by visual motion in our experimental setup.…”
Section: Mfr Initiation Mechanismmentioning
confidence: 73%